Social communication through social media - An applied study on some platforms - melizi, yaakoub (Journal of Social Sciences and Humanities, 2024)
Social communication is one of the forms of communication used by public authorities, private institutions and associations of all kinds, in order to spread awareness among individuals and mobilize them to the importance of adopting new ideas and behaviors to attain a conscious civilized society, away from social problems and wrong deeds. For achieving this objective, these institutions and associations use several means of communication, most notably social media, which provide a lot of flexibility to reach the largest number of target audience of social communication campaigns. These media have also availed the immediate interaction via the virtual space with the targeted individuals, and have paved the way for discussions and dialogues, which have contributed to increase the impact on individuals and urging them to adopt new ideas or behaviors and abandon all negative ones, including achieving the objective of social communication.